CCR7 Receptor Expression in Mono-MAC-1 Cells: Modulation by Liver X Receptor α Activation and Prostaglandin E2 - Bérengère Tanné; Stéphane Bernier; Nancy Dumais (International Journal of Inflammation)
Cell migration via chemokine receptor CCR7 expression is an essential function of the immune system. We previously showed that prostaglandin E2 (PGE2), an important immunomodulatory molecule, increases CCR7 expression and function in monocytes. Here, we explore the role of the liver X receptor α (LXRα) activation on CCR7 expression in Mono-Mac-1 (MM-1) cells in the presence of PGE2. To do this, MM-1 cells were stimulated with the LXRα synthetic agonist T0901317 in the presence or absence of PGE2. CCR7 mRNA transcription was measured using quantitative RT-PCR and protein expression was examined using flow cytometry. CCR7 function was analyzed using migration assays in response to CCL19/CCL21, which are natural ligands for CCR7. Our results show that agonist-mediated activation of LXRα in the presence of PGE2 increases CCR7 mRNA transcription and MM-1 cell migratory capacity in response to CCL19/21. In addition, our results demonstrate that engagement of the E-prostanoids 2 and 4 (EP2/EP4) receptors present on MM-1 cells is responsible for the observed increase in CCR7 mRNA expression and function during LXRα activation. Examination of monocyte migration in response to lipid derivatives such as PGE2 and oxysterols that are produced at sites of chronic inflammation would contribute to understanding the excessive monocyte migration that characterizes atherosclerosis.